The Influence of Supervision of Learning and Communication on The Performance of Educators in Madrasah Aliyah YMPI Rappang, Sidenreng Rappang District - Tenriningsih, Andi (Universitas Islam Negeri Alauddin Makassar, 2021)
Implementation of educational programs requires supervision. Supervision is responsible for the effectiveness of the planned program. Educational supervision in schools is more directed at increasing the ability of teachers in order to improve the teaching and learning process with the principal as the supervisor. The results of research conducted at Madrasah Aliyah YMPI Rappang showed that the level of supervision of the principal was in the sufficient category, based on the established assessment criteria, namely: class visits, encouraging teacher work, providing curriculum understanding, developing learning methods, meetings and coaching as well as activities. routine outside of teaching hours. Meanwhile, the performance of teaching staff (teachers) at Madrasah Aliyah YMPI Rappang shows that the quality and quantity of work is good, because most of the respondents are in the good category (55.56%). Assessment of the quality and quantity of the teaching force is based on the quantity of work, cooperation, support, and positive feelings. In this study, the results of hypothesis testing were also obtained which indicated that there was a positive influence between the supervision of the principal on the performance of the Madrasah Aliyah YMPI Rappang teachers.